Presenting a Model of Effective Factors in the Intention to Use Information Technology in Teaching and Learning - Saeid Talebi; Saeid Mazlomian; Ahmad Reza Akbari; Afifeh Davodi (Kerman University of Medical Sciences, 2015)
Background & Objective: The present study presents a model of effective factors in the intention to use information technology (IT) in teaching and learning among students of Payame Noor University and Shiraz University of Medical Sciences Iran Methods: This was a crosssectional study performed using Krejcie and Morgan s (1970) formula and by considering unreturned questionnaires and eliminating incomplete questionnaires The 120 questionnaires from students of Shiraz University of Medical Sciences and 317 questionnaires from Payame Noor University of Fars province were analyzed using path analysis and AMOS software Results: The results show that the impact of perceived ease of use on students intention to use IT is higher in Payame Noor University students (0338) than Shiraz University of Medical Sciences (0204) The impact of perceived usefulness on intention to use IT was higher among Shiraz University of Medical Sciences (0280) than Payame Noor University students (0218) Moreover the impact of goal achievement on perceived ease of IT use was higher in Payame Noor University students (0356) than Shiraz University of Medical Sciences students (0255) No significant differences were observed between the students of Shiraz University of Medical Sciences and Payame Noor University in other paths Conclusion: The data showed acceptable and favorable fitting with the model Based on the confirmed hypothesis the causal model presented in this study is an appropriate model for universities and other educational institutions that apply technologybased learning as an important strategy in their virtual courses